Perbandingan DNN dan CNN dalam Klasifikasi Kata-Kata Kasar pada YouTube Shorts - Evan Febditya Pratama; Ryan Ari Setyawan; Jemmy Edwin Bororing (Universitas Pancasakti, 2026)
Abusive words in YouTube Shorts are difficult to moderate because harmful expressions may appear in captions, comments, or embedded text within visual frames. This study compares the performance of a Deep Neural Network (DNN) and a Convolutional Neural Network (CNN) for abusive-word classification using text and image features from YouTube Shorts content. The dataset consisted of 1,013 image-text samples labeled into two binary classes: abusive and non-abusive. Textual features were derived from the text column representing OCR/caption information and transformed into 2,500-dimensional features, while image features were obtained from RGB images resized to 96 by 96 pixels. The dataset was divided into training, validation, and testing subsets consisting of 658, 202, and 153 samples, respectively. Both models were trained using dropout, L2 regularization, early stopping, and image augmentation. The results show that CNN outperformed DNN, achieving test accuracy of 0.8627 and macro F1-score of 0.8527, compared with DNN accuracy of 0.8301 and macro F1-score of 0.8195. These findings indicate that CNN provides more effective multimodal classification performance for detecting abusive words in YouTube Shorts content.